Rancang Bangun Sistem Kontrol Alat Pakan Kucing Otomatis Dengan Arduino Mega 2560 Dan Motor Servo - Teten Dian Hakim; Manson Hutagaol (JURNAL ELEKTRO, 2024)
Cats is one of the most popular animals in the world that have various breeds. One of the most popular types is Persian and Angora. It requires discipline and persistence both in maintaining cleanliness and also in providing food in caring cats. Constraints in feeding cats are due to the routine activities of the owner outside the home, so providing cat food every day cannot be controlled properly and can make cats more susceptible to disease. This requires an automatic feeding device that can be used to assist cat owners in providing feed on a scheduled basis. This study uses a microcontroller with Arduino Uno as a control system to control input and output. RTC as a scheduled determinant will give commands to the Arduino Uno to drive the mini servo. Mini servo as the main container activator opens the main container which will later fall into the weighing container. The load cell sensor can weigh the feed which will be poured through the mini servo. The percentage that was tried was up to 99%. It works on the condition that the main container is filled with more feed. However, if the feed is filled with ¾, the feed that comes out will be more precise